Evaluating baculovirus mixtures against false codling moth Thaumatotibia leucotreta Meyrick. (Lepidoptera: Tortricidae) - Tole, Siviwe (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Bioinformatics)
False codling moth (FCM), Thaumatotibia leucotreta, is an important pest of citrus, stone fruit, avocados, peppers, and other important agricultural crops in southern Africa. Baculovirus-based biopesticides are components in an integrated pest management (IPM) programme to manage the pest in the field. Cryptogran™ and Cryptex™ which are CrleGV-SA based-biopesticides have been effective in the control of T. leucotreta for the past 15 years. Recently, CrpeNPV-based Multimax™ and Codlmax™ have been commercialised to control T. leucotreta and other important agricultural pests. Despite these viruses being relatively host-specific and safe to humans and animals in comparison to chemical insecticides, their application is hindered by their slow speed of kill, sensitivity to UV light, and the potential for insect resistance. Research investigating the effects of mixed baculoviral interactions against target pests has been a growing field of interest due to their potential to overcome such shortcomings. Previous studies using a combination of CrleGV-SA and CrpeNPV against T. leucotreta observed a reduction in lethal concentration in laboratory bioassays, indicating that such mixtures may have the potential for application in the field. This has led to the motivation to investigate further interactions between CrleGV-SA in combination with CrpeNPV, CpGV-M, and HearNPV-Au to understand better how these viruses interact and to determine whether synergistic, additive, or antagonistic interactions can occur against T. leucotreta. The outcome of these interactions will inform researchers and farmers about best practices concerning these viruses should they be combined against T. leucotreta in the future. Prior to performing mixed baculovirus infections in laboratory bioassays, oligonucleotides targeting unique regions in the viral genomes of CrleGV-SA, CrpeNPV, CpGV-M, and HearNPV-Au were designed using Primer-BLAST. The specificity of these oligonucleotides was further tested in silico using Geneious R11 software (11.1.5). The stocks of CrpeNPV, CpGV-M, and HearNPV-Au were purified using crude OB extraction from diseased C. peltastica, C. pomonella, and H. armigera larval cadavers provided by River Bioscience (Pty) Ltd (Gqeberha, South Africa). The stock of CrleGV-SA was purified using crude OB extraction from infected T. leucotreta cadavers. Subsequently, the unique oligonucleotides were used in PCR assays to detect if the samples contained the baculoviruses of interest. Amplicons of the expected sizes were generated indicating the presence of CrleGV-SA, CrpeNPV, CpGV-M, and HearNPV-Au in each of the samples. The OBs were counted using darkfield microscopy and a counting chamber before the single and mixed infections were initiated against T. leucotreta neonate larvae. Surface-dose biological assays were used to evaluate the relative virulence in terms of lethal concentration of CrleGV-SA, CrpeNPV, and CpGV-M, alone against T. leucotreta. After 7 days, the dose mortality data was analysed using "drc" in R studio and the LC50 and LC90 were compared amongst each virus. The CrleGV-SA treatment was estimated to be the most virulent in comparison to CrpeNPV and CpGV-M. A dose discriminate assay confirmed that HearNPV does not cause mortality in T. leucotreta. Similarly, the relative virulence in terms of lethal concentration of CrleGV-SA in various ratios in combination with CrpeNPV, CpGV-M, and HearNPV-Au was determined using 7-day surface dose biological assays. The CrleGV/CrpeNPV was the most virulent mixture with lower LC50 and LC90 values measured in comparison to CrleGV/CpGV and CrleGV/HearNPV, respectively. The Tammes Bakuniak graphic method confirmed the CrleGV/CrpeNPV, CrleGV/CpGV, and CrleGV/HearNPV mixtures to be antagonistic against T. leucotreta neonate larvae in terms of lethal concentration. The last aspect of the study was to determine the probable cause of larval death. A modified CTAB protocol was used to extract genomic DNA from neonate-sized T. leucotreta cadavers collected in single and mixed infection assays. The gDNA served as templates in PCR assays using the unique oligonucleotides. In single infections, the presence of CrleGV-SA in CrpeNPV and HearNPV inoculated larvae was observed. The results suggest possible covert infections of CrleGV-SA in the T. leucotreta colony which may be caused by virus infection or an unknown stress factor. The results from the mixed infections showed the presence of each virus in all replicates except for the CrleGV/CpGV and CrleGV/HearNPV mixtures. In the CrleGV/CpGV mixture, only CrleGV-SA was present in the last replicate, suggesting a possible competition for host resources. In the CrleGV/HearNPV mixture, only CrleGV-SA was detected in all 3 replicates, suggesting that HearNPV did not have any effect and the larvae died of the CrleGV-SA infection. This is the first study to report mixtures of CrleGV-SA in combination with CpGV-M and HearNPV-Au against T. leucotreta neonate larvae. Despite the antagonistic interactions observed in the evaluated mixtures, this study has laid a foundation to further investigate how these viruses interact in dual infections for the improved control of T. leucotreta. This may be done by evaluating different ratios and combinations of baculoviruses to those used in this study.
Keywords: False codling moth -- Biological control; Baculoviruses; Integrated pest management; Natural pesticides; Granulovirus